The Relationship Between A History of Bladder Cancer and The Risk of Urethral Tumors : A Systematic Review - Al Azwar Fachrul Rezy; Keke Khairani (International Medical Journal Corp. Ltd, 2026)
Background: Bladder cancer survivors face a lifelong risk of secondary urothelial tumors due to field cancerization. Urethral recurrence (UR) after radical cystectomy (RC) is a serious but variable event. This systematic review synthesizes evidence on the relationship between a history of bladder cancer and the subsequent risk of urethral tumors. Methods: We systematically screened RCT, etc (up to 2026) that involved human participants with documented bladder cancer, reported urethral tumor outcomes, and provided temporal data. Data extraction focused on study design, bladder cancer characteristics, urethral tumor incidence, risk estimates, and confounders. Results: Pooled UR incidence after RC ranged from 1% to 14%, most commonly 4–5% (1–3). Orthotopic neobladder (ONB) diversion significantly reduced UR risk (OR 0.44; 95% CI 0.24–0.79) across three independent meta-analyses (1,4,5). Prostatic urethral involvement was the strongest predictor (HR 5.35–7.95) (2,4,12). Positive urethral margins conferred the highest individual risk (HR 18.33) (12). Male sex (OR 3.16) and tumor multifocality (HR 2.97) were also significant (4). Concomitant CIS showed inconsistent significance. Asymptomatic detection of UR reduced mortality by 30% (HR 0.69) (8). Simultaneous TURBT+TURP did not increase prostatic urethral recurrence (OR 1.06) (71). Discussion: A history of bladder cancer confers a well-defined urethral recurrence risk, strongly modified by diversion type and prostatic involvement. ONB provides a protective mechanical washout effect. Prostatic stromal invasion carries worse prognosis than mucosal involvement. Surveillance-detected UR has better survival. Simultaneous endoscopic surgery appears oncologically safe. Conclusion: Bladder cancer history is a significant risk factor for urethral tumors. Risk-stratified surveillance (urethral wash cytology, urethroscopy in high-risk patients) and orthotopic diversion where feasible are recommended. Prophylactic urethrectomy should be reserved for very high-risk cases.